Analysis of features of fiber components on the basis of periodic structures - Филипенко, Александр Иванович; Жарикова, Ирина Владимировна (Eastern-European Journal of Enterprise Technologies, 2009)
The problems associated with the peculiarities of specialized optical fiber with Bragg gratings (BG) are considered. Review that given in the article can be used to develop new applications based on BG, and described model of such arrays allow for analysis of the impact of external factors on the parameters of devices based on them